Parent Education and Training for autism spectrum disorders: Scoping the evidence. (January 2020) - Dawson-Squibb, John-Joe; Davids, Eugene L; Harrison, Ashley J; Molony, Maggie A; de Vries, Petrus J
Empowering families of children with autism spectrum disorder through education and training is best practice. A wide range of Parent Education and Training programmes are delivered around the globe, but there is limited knowledge about the characteristics of these programmes, or about the research methods and outcomes used to evaluate them, particularly in countries outside the United States. We, therefore, performed a scoping review of all peer-reviewed Parent Education and Training publications outside the United States. A search was conducted between March and May 2017. Four reviewers extracted data and performed a mixed-methods quality appraisal of publications. Thirty-seven publications representing 32 unique programmes were identified. Publications described a highly diverse range of Parent Education and Training programmes across 20 countries and all continents except South America. The majority were group-based, but varied significantly in goals, modalities and duration. The majority of studies (86.4%) reported positive outcomes in relation to the core study objectives and only two studies reported some negative findings. Quality appraisal rated only 27% of studies to have met all the methodological quality criteria. Implementation factors such as manualisation, fidelity and cost were commented on infrequently. In spite of the clear need for Parent Education and Training programmes, our findings show that the research evidence-base in autism spectrum disorder outside the United States is relatively small, non-representative and in need of methodological quality improvements.